Relationship Between Discipline with Performance Hospital Administration Officer in the Era of the Covid-19 Pandemic - Devi Pramita Sari; Watcharapong Moolmirat; Fatma Siti Fatimah; Sherly Listyaningsih (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Performance is the work of a person or group of people in an organization based on their duties and responsibilities. Good performance can be achieved by increasing work discipline. Based on the preliminary study, it is known that there is 1 hospital administration officer who is not disciplined and his performance is not good. This study aims to determine the relationship between work discipline and the performance of hospital administrative officers. This research was conducted using a descriptive quantitative survey with a cross sectional study approach. The population and research samples were taken by total sampling, namely all hospital administration officers as many as 5 respondents. The research instrument used a questionnaire. Quantitative data analysis used the chi-square relationship test. The results of this study from 5 respondents based on the results of the Chi-Square test, the significance of p between the independent variables, namely public knowledge and the dependent variable of compliance with the use of masks was 0.002 (p <0.05), then Ho was rejected and it was stated that there was a relationship. The conclusion is that there is a relationship between work discipline and the performance of hospital administrative officers. Suggestions should provide knowledge of the importance of work discipline for Hospital Administration Officers.